The Police Genre and Marxist Criticism - Dardón, Juan M. (2022)
An investigation is carried out on the Marxist critique of the police genre (Foucault, Gramsci, Eisenstein and Mandel), focusing on methodological and theoretical assumptions that we have baptized as good Marxist morality. From a series of bourgeois categories, popular culture is analyzed as an accomplice or servile element of the capitalist order and state control and its ideological regime. The conceptual contributions that these authors have made about the police, differentiating the theoretical and class prejudices put into play, have been addressed separately.